Transition metal phosphides: new generation cathode host/separator modifier for Li-S batteries - Huang, Song; Huixiang, Edison; Yang, Yang; Zhang, Yufei; Ye, Minghui; Li, Cheng Chao (Journal of materials chemistry. A, Materials for energy and sustainability, 2021)
Owing to their promising applications including, aircrafts, military field, and submarines, lithium-sulfur (Li-S) batteries with high energy density (2500 W h kg −1 ) are emerging as the next-generation energy storage system with low cost to replace lithium-ion batteries. Nevertheless, the road to commercialization is mainly hindered by low coulombic efficiency, poor cycling, and rate capabilities, which are mainly due to the so-called polysulfide (PS) shuttle, sluggish electrochemical reactions, etc. One of the most effective and direct strategies among different optimization methods is to rationally design the cathode host of Li-S batteries. Transition metal phosphides (TMPs) feature relatively good electrical performance, mild synthesis, adequate chemical adsorption strength and exceptional catalytic capability for PS, which make them a cathode host/separator modifier for the new generation of Li-S batteries. In this review, the electrochemical reaction mechanisms of Li-S batteries and major roadblocks to commercial applications are firstly described. Following that, we summarize the synthesis strategy of TMPs and systematically review the recent progress on TMPs in Li-S batteries, where light is shed on the specific roles of TMPs as Li-S battery cathodes and separator modifiers, and briefly on the synthesis. In future research on Li-S batteries, the review provides insight into the challenges of TMPs and directions for further development. This article summarizes the latest progress on TMPs for Li-S batteries in recent years, with a particular focus on the adsorption and catalysis of TMPs to PS, also including synthesis strategies, challenges and opportunities in the future.